2014
DOI: 10.1245/s10434-014-3559-z
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiotherapy Affects the Indications for Lateral Pelvic Node Dissection in Mid/Low Rectal Cancer with Clinically Suspected Lateral Node Involvement: A Multicenter Retrospective Cohort Study

Abstract: In mid/low rectal cancer with clinically metastatic LPNs, the decision to perform LPND should be based on the LPN response to nCRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 34 publications
3
87
1
Order By: Relevance
“…Because patients with locally advanced lower rectal cancer developed lung metastases at twice the rate of liver metastases following surgery, careful screening for lung metastasis should be considered during follow-up surveillance. Most LPNs in our patients were downsized by administering CRT regardless of the presence of metastasis, as was the case in previous studies [15,16]. Neoadjuvant CRT has been shown to reduce the number of harvested mesorectal lymph nodes during pathological assessment [17], and this phenomenon was previously reported to be caused by lymphocyte depletion, atrophy of the stroma, and replacement by adipocytes [18].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Because patients with locally advanced lower rectal cancer developed lung metastases at twice the rate of liver metastases following surgery, careful screening for lung metastasis should be considered during follow-up surveillance. Most LPNs in our patients were downsized by administering CRT regardless of the presence of metastasis, as was the case in previous studies [15,16]. Neoadjuvant CRT has been shown to reduce the number of harvested mesorectal lymph nodes during pathological assessment [17], and this phenomenon was previously reported to be caused by lymphocyte depletion, atrophy of the stroma, and replacement by adipocytes [18].…”
Section: Discussionsupporting
confidence: 72%
“…Oh et al [16] investigated 66 patients with mid/low rectal cancer who had suspected LPN metastases and who underwent preoperative CRT and LPN dissection; they found that the overall and disease-free survival rates of patients with persistently enlarged LPNs after CRT were poorer. In contrast, Akiyoshi et al [11] reported no association between LPN size and prognosis after analyzing 77 patients with low rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that nodal responses tend to mirror the response of the primary tumor, with ypN + rates ≤ 5% in patients with ypT0 disease . Lymph node size, morphology, or both, typically based on MRI, appear to correlate with residual metastases . The reported accuracy of MRI in assessing complete response in initially involved lymph nodes ranges from 80% to 90%, with additional techniques such as contrast enhancement potentially improving these rates .…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the posttreatment stage is more useful for accurately predicting the outcomes than the clinical stage. In addition, reports from Korea have suggested that the decision to perform lateral lymph node dissection should be based on the lateral lymph node response to CRT 65) . In contrast, Akiyoshi et al showed that MRI before CRT was useful in predicting lateral lymph node metastasis and determining the indications for lateral lymphadenectomy 22) .…”
Section: D the Usefulness Of Lateral Lymph Node Dissection Followinmentioning
confidence: 99%